Psychological Effects in the Relationship of Digital Human Resource Management to Employee Resilience: A Literature Review - Santy Berliana Naibaho; Hendy Tannady; Lista Meria; Ferryal Abadi; Rojuaniah Rojuaniah (Kuras Institute, 2025)
The COVID-19 pandemic has created rapid changes that led many companies to speed up digital transformation, particularly in the management of human resources. A key development in this process is the adoption of Digital Human Resource Management (DHRM), an approach that brings digital technologies into HR functions. This study aims to systematically review the literature linking DHRM to employee resilience, focusing on the psychological impact of the interaction between technology and individuals. Using a systematic literature review (SLR) method, 50 articles from Scopus and ProQuest were analyzed. The results show that DHRM contributes to employee psychological resilience by increasing self-efficacy, psychological safety, and agility and creating an emotionally supportive digital workspace. The study found that psychological aspects like coping strategies, emotions, and perceived support are essential in linking digital systems with employee resilience. The study suggests using an interdisciplinary perspective that brings together technology and psychology to develop effective DHRM systems while also addressing employees’ psychological well-being.